Double blind comparison of the effects of cimetidine, ranitidine, famotidine, and placebo on intragastric acidity in 30 normal volunteers. Issue 1 (January 1988) - Merki, H S; Witzel, L; Walt, R P; Neumann, J; Scheurle, E; Mappes, A; Krammisch, H; Heim, J; Kaufmann, D; Roehmel, J
Abstract : Continuous measurement of 24 hour intragastric acidity was carried out in 30 normal volunteers during treatment with placebo, cimetidine 800 mg, ranitidine 300 mg, and famotidine 40 mg in a double blind study. Medication was taken after the evening meal (post cenam nocte, PCN). Median 24 hour acidity decreased with all H2-receptor antagonists from 25.1 mmol/l on placebo to 10 mmol/l (-60.1%) during cimetidine, to 3.2 mmol/l (-87.25%) during ranitidine and to 2.5 mmol/l (-90.0%) during famotidine treatment (p less than 0.0005). All drugs significantly inhibited night time acidity but only famotidine decreased acidity during the late morning compared with placebo. Significantly greater acid reduction was seen with famotidine and ranitidine compared with cimetidine but no difference was found between famotidine and ranitidine.